First record of intersexual phenotype in Calliopsini bees (Hymenoptera, Apidae, Andreninae): an unusual specimen of Acamptopoeum submetallicum (Spinola) - Ramos, Kelli S.; Ruz, Luisa (Zootaxa, 2013)
Sex anomalies are one of the best-known cases of teratology among wild bees with different terms used to differentiate among such abnormalities. Gynandromorphs are individuals with genetically distinct male and female tissues while intersexes are genetically uniform individuals with expression of sexual features of the opposite sex. Among the three commonly accepted gynandromorph categories—bilateral symmetry, transverse and mixed (or mosaic)—the relative proportion of each gynanders category described in the literature shows the transverse and mosaic as the most frequently observed cases among wild bees (Michez et al. 2009; Hinojosa- Díaz et al. 2012). In bees, gynandromorphs are recorded from 117 species in 30 genera of all families being mostly recorded from the long-tongued bees in Apinae and Megachilinae (Wcislo et al. 2004; Michez et al. 2009; Hinojosa-Díaz et al. 2012, Lucia et al. 2012).